2002
DOI: 10.1002/jrs.953
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational spectra of racemic and enantiomeric malic acids

Abstract: The IR and Raman spectra of racemic (DL-) and both enantiomeric (L-and D-) forms of malic acids and also their silver salts and deuterated analogues were measured in the polycrystalline state in the range 4000-100 cm −1 . Significant differences in the spectra of the racemic and enantiomeric forms of malic acid were described for the first time and are discussed in relation to the structural features, including crystal symmetry, geometric parameter distinctions and hydrogen bonding. The most significant spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 12 publications
(13 reference statements)
4
23
0
Order By: Relevance
“…We have previously characterized P2Y 1 and P2Y 2 receptors in glioma C6 cells using measurements of [Ca 2+ ] i and demonstrated that ADP, ATP and UTP initiated a large Ca 2+ response consistent with the typical capacitative model of Ca 2+ entry, associated with the stimulation of PLC and depletion of intracellular Ca 2+ stores [15]. In this process, the initial rise in [Ca 2+ ] i results from the direct effect of InsP 3 on the endoplasmic reticulum and can be observed even in the absence of extracellular Ca 2+ [28]. Our previous study showed that such Ca 2+ responses were observed for all three nucleotides [15].…”
Section: Discussionsupporting
confidence: 55%
“…We have previously characterized P2Y 1 and P2Y 2 receptors in glioma C6 cells using measurements of [Ca 2+ ] i and demonstrated that ADP, ATP and UTP initiated a large Ca 2+ response consistent with the typical capacitative model of Ca 2+ entry, associated with the stimulation of PLC and depletion of intracellular Ca 2+ stores [15]. In this process, the initial rise in [Ca 2+ ] i results from the direct effect of InsP 3 on the endoplasmic reticulum and can be observed even in the absence of extracellular Ca 2+ [28]. Our previous study showed that such Ca 2+ responses were observed for all three nucleotides [15].…”
Section: Discussionsupporting
confidence: 55%
“…The results for the known racemic and enantiomer phases agree with data reported in the works 26,63 and do not contradict other literature findings. 67 Phase relationships in the (S)-malic acid-(R)-malic acid system. The TRPXRD method showed that the racemic phases RSI and RSIII do not undergo polymorph transformations until the substances reached their melting points at 124°C and 123°C, respectively.…”
Section: The System (S)-malic Acid-(r)-malic Acidmentioning
confidence: 99%
“…An increase in pH from 6 to 11 causes a decrease in the adsorption of malate ions on hydroxyapatite and indicates a competitive exchange of malate ions for hydroxyl ions in hydroxyapatite. This mechanism is confirmed by the increase (Baranska et al 2003) Fig. 9 Effect of malate ion adsorption on HAp on the zeta potential as a function of solution pH in acidity of the groups on the surface of hydroxyapatite due to the adsorption of malate ions.…”
Section: Discussionmentioning
confidence: 67%
“…The analysis of absorption bands in the spectrum presented in Fig. 8 to DL malic acid (Baranska et al 2003). A spectrum of carbonate characteristic band appears at 1484 cm −1 that may have caused CO 2 adsorption during the sample preparation.…”
Section: Resultsmentioning
confidence: 95%